Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) - Novianti, Ardya ; Epi, Yus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
SAK EMKM aims to make it easier for SMEs to gain access to funding from various financial institutions, so the presence of SAK EMKM is expected to help SMEs in Indonesia in preparing financial reports. The problem that often occurs is that SMEs are not yet able to make financial reports. This research aims to prepare financial reports for the laundry service business